Construction of PARI public health education programs for Chinese undergraduates: a Delphi study - Kong, Yuzhe; Xu, Haitao; Li, Chuyan; Yang, Yang; Zhu, Xiaoyi; Zuo, Yu (Frontiers in Public Health, 2024)
Objectives The objective of this study is to develop a consensus among experts on a comprehensive and scientifically sound physical activity-related injuries (PARI) public health education program specifically tailored for undergraduates. Methods This study designed three rounds of expert consultation by using a Delphi method. A panel of 30 experts from the fields of public health education, sports medicine, anesthesia pain, emergency medicine, and emergency nursing participated in the study. Results This study successfully established a consensus among experts on the goals, content, teaching methods, and time allocation for the PARI Public Health Education Program for undergraduates. The program encompasses 10 objectives divided into 2 main categories: professional knowledge and skill goals. In terms of content, it includes 5 primary indicators, 22 secondary indicators, and 56 detailed tertiary indicators. Six teaching methods were identified as suitable. Additionally, a typical 60-min educational session was segmented into eight parts, with a proposed time arrangement for each, ensuring comprehensive coverage of all topics. Conclusion The consensus achieved in this study on the PARI Public Health Education Program for undergraduates lays a crucial foundation for the advancement of health literacy and proactive health management within this demographic. We presented a comprehensive framework for PARI public health education, integrating diverse learning methods and content areas. This systematic approach not only enriched the resources available for undergraduate health education, especially of PARI but also had the potential to significantly impact the implementation and effectiveness of health promotion strategies.